2016
DOI: 10.1007/s11325-016-1319-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPAP therapy on cardiovascular events and mortality in patients with obstructive sleep apnea: a meta-analysis

Abstract: CPAP therapy was associated with a trend of decreased risk of cardiovascular events. Furthermore, ESS and BP were significantly lower in the CPAP group. Larger randomized studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 34 publications
5
37
2
Order By: Relevance
“…However, our meta-analysis revealed no significant treatment effect of CPAP on cardiovascular events in nonsleepy OSA patients. A recently published meta-analysis about the effect of CPAP therapy on cardiovascular events (38) had a similar finding that CPAP could not decrease the risk of cardiovascular events compared with the control group (OR, 0.84; 95% CI, 0.62-1.13; P=0.25). Considering the limited number of people included and the short duration of follow- up, the negative results in our meta-analysis could not exclude the possibility that non-sleepy OSA patients could benefit from long-term CPAP use.…”
Section: Discussionmentioning
confidence: 79%
“…However, our meta-analysis revealed no significant treatment effect of CPAP on cardiovascular events in nonsleepy OSA patients. A recently published meta-analysis about the effect of CPAP therapy on cardiovascular events (38) had a similar finding that CPAP could not decrease the risk of cardiovascular events compared with the control group (OR, 0.84; 95% CI, 0.62-1.13; P=0.25). Considering the limited number of people included and the short duration of follow- up, the negative results in our meta-analysis could not exclude the possibility that non-sleepy OSA patients could benefit from long-term CPAP use.…”
Section: Discussionmentioning
confidence: 79%
“…The analysis indicated that the severity of OSA was associated with a stronger impact of CPAP on systolic BP (47). The beneficial effect of CPAP on BP and the effect size were confirmed by successive meta-analyses (73,74). Patients with severe OSA or treatment-resistant hypertension were reported to have the most clinically relevant effects.…”
Section: Osamentioning
confidence: 89%
“…Continuous positive airway pressure (CPAP) therapy can lower the risk of HTN (115). However, due in part to low long-term adherence to CPAP therapy, meta-analyses indicate that CPAP therapy for OSA results in only small (1–2 mmHg) average reductions in BP (116118) - levels not sufficient to bring HTN under control nor large enough to reduce risk of stroke or coronary heart disease (119). Treatment with antihypertensive drugs yields larger long-lasting reductions in BP in populations with OSA who do not use CPAP (120122), but, these drugs fail to generate the reductions obtained in HTN patients without OSA (123).…”
Section: Resultsmentioning
confidence: 99%